A Base‐Controlled Reaction of 2‐Cyanoacetamidines (3, 3‐Diaminoacrylonitriles) with Sulfonyl Azides as a Route to Nonaromatic 4‐Methylene‐1, 2, 3‐triazole‐5‐imines. Issue 24 (5th June 2020) - Silaichev, Pavel S.; Beryozkina, Tetyana V.; Novikov, Mikhail S.; Dehaen, Wim; Bakulev, Vasiliy A.
Abstract : Reactions of 2‐cyanoacetamidines with sulfonyl azides were shown to take place via two different pathways to form a mixture of 1‐substituted 5‐amino‐1, 2, 3‐triazoles 3 and novel 4‐methylene‐1 H ‐1, 2, 3‐triazole‐5(4 H )‐imine derivatives 4–14 . In the absence of a base, 5‐amino‐1, 2, 3‐triazoles 3 are formed as the only products. The presence of 1.2 equiv. of sodium ethoxide or DBU switches the reaction outcome while involving the cyano group, resulting (after a 1, 5‐protic shift) in triazoles 4–14 as the only products. The methods were elaborated for the selective and efficient synthesis of triazoles 3 and 4‐methylene‐1, 2, 3‐triazole‐5‐imines 4–14 including one‐pot synthesis from sodium azide and sulfonyl chlorides. The unusual structure of 4–14 compounds was confirmed by X‐ray data and 2D 1 H– 15 N and 1 H– 13 C NMR spectra. The formation of the products was explained by the presence of two strong hydrogen bonds N··· H and O··· H in these molecules. Abstract : The generally accepted opinion on the single diazo group transfer direction of methylene active amidines with sulfonyl azides has been disproved by this study. Thus, the reaction of 2‐cyanoacetamidines with sulfonyl azides afforded different types of 1, 2, 3‐triazoles. Mesyl azide reacts with 2‐cyanoacetamidines in the absence of a base to afford 5‐amino‐4‐cyano‐1, 2, 3‐triazole. The use of a strong base switches the direction of the reaction in favor of nonaromatic 4‐methylene‐1, 2, 3‐triazole‐5‐imines.